2021
DOI: 10.32604/or.2022.03561
|View full text |Cite
|
Sign up to set email alerts
|

PRPF6 promotes metastasis and paclitaxel resistance of ovarian cancer via SNHG16/CEBPB/GATA3 axis

Abstract: Metastasis and paclitaxel (PTX) resistance are the main reason for the poor prognosis of ovarian cancer (OC).Evidence showed that RNA-binding proteins (RBPs) and long noncoding RNAs (lncRNAs) can modulate posttranscriptional regulation. The aim of this study was to determine the relationship among RBP, lncRNA and OC and to further guide clinical therapy. Immunohistochemistry revealed that pre-mRNA processing factor 6 (PRPF6) was upregulated in OC chemoresistant tissues and was closely related to advanced (Fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…When GPX3 is inhibited by RNA interference, the sensitivity of clear cell adenocarcinoma cells to cisplatin increases. Following GPX3 inhibition, tumor cells may proliferate, enhancing drug accumulation within the cells (73,77).…”
Section: Ocscs and Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…When GPX3 is inhibited by RNA interference, the sensitivity of clear cell adenocarcinoma cells to cisplatin increases. Following GPX3 inhibition, tumor cells may proliferate, enhancing drug accumulation within the cells (73,77).…”
Section: Ocscs and Markersmentioning
confidence: 99%
“…Recently, the interest among researchers in the role of non-coding RNAs in the regulation of tumorigenesis and development is growing. Wang et al (77) conducted a study that focused on the small nuclear kernel RNA host gene 16 (SNHG16)/Enhancer binding protein β(CEBPB)/GATA3 axis and its influence on precursor mRNA processing factor 6 (PRPF6) and GATA3 expression. The findings of their study revealed that PRPF6 promotes the expression of GATA3 by inducing SNHG16 (77).…”
Section: Ocscs and Markersmentioning
confidence: 99%
See 1 more Smart Citation